What factors influence termination behaviour on freemium platforms? An empirical analysis of the termination probability among paying users - Nina Lehmann-Zschunke (Journal of Consumer Behaviour, 2024)
Because of growing digitalization, consumers are confronted with more and more new technologies. Digital ecosystems and digital platforms are of great importance in this context. One possibility for monetizing the services offered on digital platforms is the freemium pricing model. In light of increasing competition, it is important for platform operators to know as much as possible about the usage behaviour of their consumers. In particular, they need to know what factors influence the termination behaviour of paying users. The empirical study is based on data from 20,319 paying users of a freemium platform that offers information on equestrian sports. Using a logistic regression, several possible influencing factors on the probability of termination are examined. Among other things, the study shows that the termination probability is greater if the paying user has chosen a shorter subscription. Users who have already terminated their subscription before their current one are also at greater risk of churn. Premium users with high levels of involvement and members who receive notifications about new content on the platform are less likely to quit. The number of video views is also negatively related to the termination probability. Freemium providers can use this information to predict terminations and take appropriate action, such as special offers for users at risk of termination.
Keywords: 320